Now entering Addamsville - Zappia, Francesca (Greenwillow Books, an imprint of HarperCollins Publishers, 2021)
"Addamsville is full of ghosts. They haunt the old coal mine, take long walks along the lake, and spy from the storefronts. In Addamsville, ghosts and their stories are a way of life, attracting the visitors who keep this small town alive. But Zora knows that the ghosts are real and not some tourist trap. And she knows what else lies hidden in the darkness. Now Zora is being framed for a crime she didn't commit. With the supernatural running amok, she must track down the true culprit, clear her name, and protect her family and friends--her entire town--frome creatures set on destruction. But in a small town obsessed with ghosts, getting people to believe the truth might prove to be impossible." -- Back cover.